The neuroprotective effect of prostaglandin E2 EP1 receptor inhibition has a wide therapeutic window, is sustained in time and is not sexually dimorphic - Abe, Takato (2008)
We investigated the preclinical characteristics of the neuroprotective effect of the prostaglandin E2 type 1 receptor (EP1) antagonist SC51089 in models of focal cerebral ischemia produced by occlusion of the mouse middle cerebral artery (MCA). We found that systemic administration of SC51089 (5 to 20 μg/kg; i.p.) reduces the brain injury produced by transient (−50% ± 8%; n = 12; P < 0.05) or permanent (−39% ± 7%; n = 12; P < 0.05) MCA occlusion. SC51089 was effective even when administered up to 12 h after ischemia. The protective effect was observed both in male and female mice and was sustained for at least 2 weeks after induction of ischemia. The reduction in injury volume was associated with an improvement in neurological function assessed by the Bederson deficit score, the hanging wire test and the corner test. The data provide proof of principle that EP1 receptor inhibition is a potentially valuable strategy for neuroprotection that deserves further preclinical investigation for therapeutic application in human stroke.